2020
DOI: 10.3389/fpsyt.2020.599958
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Vitamin A and Vitamin D and Their Association With Symptoms in Children With Attention Deficit Hyperactivity Disorder

Abstract: Objective: To measure levels of vitamin A (VA) and vitamin D (VD) and the symptomatic association of their co-deficiencies on attention deficit hyperactivity disorder (ADHD) in Chinese children (6–9 years).Methods: Eighty-two children (69 boys and 13 girls; mean age = 7.1 ± 0.9 years at the time of the diagnosis) with ADHD were recruited as ADHD group. A total of 106 healthy children were recruited as the healthy control (HC) group. Serum levels of retinol and 25-hydroxyvitamin D (25(OH)D) of all children were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Vitamins A and D have recently emerged as micronutrients relevant to ADHD, since serum concentrations of 25(OH)D and retinol were linked with this disorder after adjustment for age, Body Mass Index (BMI), season of blood sampling, and sun exposure, and this co-deficiency was associated with symptom severity [ 55 ]. A meta-analysis of five case-control studies found that lower vitamin D status is significantly associated with the likelihood of ADHD (OR: 2.57; 95% CI: 1.09–6.04), and the meta-analysis of prospective studies conducted in 4137 participants indicated that perinatal suboptimal vitamin D concentrations are significantly associated with a higher risk of ADHD in later life (RR: 1.40; 95% CI: 1.09–1.81) [ 56 ].…”
Section: Dietary Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamins A and D have recently emerged as micronutrients relevant to ADHD, since serum concentrations of 25(OH)D and retinol were linked with this disorder after adjustment for age, Body Mass Index (BMI), season of blood sampling, and sun exposure, and this co-deficiency was associated with symptom severity [ 55 ]. A meta-analysis of five case-control studies found that lower vitamin D status is significantly associated with the likelihood of ADHD (OR: 2.57; 95% CI: 1.09–6.04), and the meta-analysis of prospective studies conducted in 4137 participants indicated that perinatal suboptimal vitamin D concentrations are significantly associated with a higher risk of ADHD in later life (RR: 1.40; 95% CI: 1.09–1.81) [ 56 ].…”
Section: Dietary Patternsmentioning
confidence: 99%
“…Even taking a more microscopic look at a nutrient-based level, children with ADHD have reduced plasma levels of important brain function trace elements, such as zinc, copper, iron, magnesium, and selenium [ 46 , 47 , 48 , 49 , 50 ]. In addition, vitamins A and D and PUFAs have emerged as nutrients to take into consideration in this disorder [ 55 , 57 ].…”
Section: Dietary Patternsmentioning
confidence: 99%
“…Finally, the role of vitamin D (25(OH)D) serum level in comorbid TD + ADHD is unclear, although observational studies and a meta-analysis revealed a lower level in a clinically significant proportion (about 50%) of children with ADHD [ 76 , 77 , 78 ]. For clarification of transdiagnostic aspects, Bond et al [ 79 ] investigated 25(OH)D in three groups (TD, n = 327; first degree relatives with tics, n = 31; first degree relatives without tics, n = 93).…”
Section: Level “Abnormal Brain Conditions”mentioning
confidence: 99%
“…The exact etiology of ADHD remains unclear. Polygene mutation, micronutrient imbalance, intestinal flora disorder, serotonin (5-HT) and catecholaminergic signaling pathway abnormalities have been confirmed to be related to the onset of ADHD, [5][6][7][8] but a unified pathogenesis theory has not yet been formed; therefore, it is particularly critical to study the mechanism of ADHD as a whole and as a system. At present, domestic and foreign scholars have used drugs (methylphenidate, tomoxetine, etc.)…”
Section: Introductionmentioning
confidence: 99%